Effects of Oxygen and Glucose on Bone Marrow Mesenchymal Stem Cell Culture. Issue 11 (29th October 2020) - Lau, Fiona; Dalisson, Benjamin; Zhang, Yu Ling; Zhao, Jing; Eliopoulos, Nicoletta; Barralet, Jake E.
Abstract: This study determines whether the viability of mesenchymal stem cell (MSC) in vitro is most sensitive to oxygen supply, energetic substrate supply, or accumulation of lactate. Mouse unmodified (wild type (WT)) and erythropoietin (EPO) gene‐modified MSC is cultured for 7 days in normoxic (21%) and anoxic conditions. WT‐MSC is cultured in anoxia for 45 days in high and regular glucose media and both have similar viability when compared to their normoxic controls at 7 days. Protein production of EPO‐MSC is unaffected by the absence of oxygen. MSC doubling time and post‐anoxic exposure is increased (WT: 32.3–73.3 h; EPO: 27.2–115 h). High glucose leads to a 37% increase in cell viability at 13 days and 17% at 30 days, indicating that MSC anoxic survival is affected by supply of metabolic substrate. However, after 30 days, little difference in viability is found, and at 45 days,  complete cell death occurs in both the conditions. This death cannot be attributed to lack of glucose or lactate levels. MSC stemness is retained for both osteogenic and adipogenic differentiations. The absence of oxygen increases the doubling time of MSC but does not affect their viability, protein production, or differentiation capacity. Abstract : An obstacle to the transplantation of cells and tissues is their survival in avascular implantation sites. Herein, it is demonstrated in vitro that mouse mesenchymal stem cell (MSC) viability in anoxia remains initially similar to normoxic culture. The availability of glucose affects anoxic MSC survival. While anoxic conditions limit MSC proliferation, stemness and protein production are retained.